Enhancing polyphenol delivery systems for effective chronic kidney disease management - Raischi, Viorica; Covaci, Ecaterina; Filip, Lorena; Hegheș, Simona-Codruța; Neumann, Oara (Editura USM, 2024)
Nature provided the inspiration and the ingredients for therapeutic medicine. More than 50% of all current medicinal drugs are made from herbal plants, roots, and fruits. According to the World Health Organization, 75% of the world's population uses plant-based medicine. These products contain only purified ingredients that may reduce the final product's antioxidant, antibacterial, and antimicrobial properties. Therefore, we aim to develop a method of extraction that may stabilize the antioxidant properties of the product. Polyphenols are organic compounds found in fruits and vegetables such as onions, grapes, berries, cherries, broccoli, and citrus. Polyphenols exhibit significant antibacterial and antimicrobial activity, antihypertensive and vasodilator effects, and antihypercholesterolemic and antiatherosclerotic activities. Conventional extraction methods, such as ultrasound-assisted extraction, solvent extraction, supercritical fluid extraction, or microwaveassisted extraction, use solvents with different polarities (ethanol, methanol, water, and chloroform) or elevated temperatures. Here, we developed a method of extraction and stabilization that involves an alcoholic solution and plantbased stabilizers.
Keywords: polyphenols; ultrasound-assisted extraction; chronic kidney disease; antioxidant activity; natural stabilizers; bioactive compounds; micelles; agricultural waste valorization; plant-based medicine; drug delivery systems; red onions; grape skins; bioavailability; nanoparticles